Knowledge mapping and visualization of personal information management literature, 1988–2020 - Nwagwu, Williams Ezinwa; Williams, Chidiebube Blossom (IFLA journal, 2022)
This study was designed to examine the structure of the literature on personal information management during the period 1988–2020 through the mapping of author and indexer keywords. The article also examines the volume, quantity and growth of personal information management literature during the period. The Scopus database was searched with the phrase ‘personal information management’ within the title, abstract and keyword fields on 18 February 2021. The annual growth in publications is presented as the number of retrieved documents each year, and the annual growth rate of publications on the subject is analysed. A total of 887 documents have been written on the subject since 1988. The major focus in addressing the problem of personal information management appears to be on technology applications, but research from 2015 onwards starts to address individual factors as they relate to personal information management.